The Influence of The Role of Parents on Children's Social Independence in The Cempaka Cluster Kindergarten, Central Banjarmasin District - Novi Suma Setyawati (International Journal of Integrated Science and Technology, 2023)
At the Gugus Cempaka Kindergarten, children Not yet show attitude independent at school. This is caused children too spoiled by parents them. Parent get used to child For independent, get what are they want, so you can Study responsible answer, esp For self yourself. Research objective : influence role to independence social children at Gugus Cempaka Kindergarten, Central Banjarmasin. Study This use approach quantitative with explanatory method, namely because consequence. Population study This totaling 360 with a sample of 189 people used technique sample proportional. Study This use questionnaire, analysis regression, and path analysis. The result show influence parental role _ to independence social children in the Cempaka Cluster Kindergarten, Central Banjarmasin District, is 15%, while factor other influence by 85%.